2019
DOI: 10.1155/2019/2864216
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Orthognathic Surgery on Patient Satisfaction, Overall Quality of Life, and Oral Health-Related Quality of Life: A Systematic Literature Review

Abstract: Several treatments have been suggested to correct dentofacial abnormalities, including orthognathic surgery. The aim of the present systematic review was to assess the impact of orthognathic surgery on patient satisfaction, overall quality of life, quality of life related to oral health—and to orthognathic surgery in particular—among adult patients. Two investigators independently reviewed the available literature in the databases PubMed/MEDLINE, LILACS, SciELO, EMBASE, Trip, and Google Scholar (gray literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 40 publications
(47 reference statements)
3
29
0
1
Order By: Relevance
“…Some studies have found that oral function, including bite, pain, smile, and speech, is a primary motivation [12][13][14]. A recent systematic review showed physiological and psychological improvement in QoL following orthognathic surgery [15]. A study with a 5-year follow-up found significant improvement and stabilization after 2-5 years in regard to the general health-related QoL, OHRQoL, and psychosocial function after BSSO [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that oral function, including bite, pain, smile, and speech, is a primary motivation [12][13][14]. A recent systematic review showed physiological and psychological improvement in QoL following orthognathic surgery [15]. A study with a 5-year follow-up found significant improvement and stabilization after 2-5 years in regard to the general health-related QoL, OHRQoL, and psychosocial function after BSSO [16].…”
Section: Introductionmentioning
confidence: 99%
“…Most of those questionnaires were not properly validated, and only the orthognathic QOL questionnaire (OQLQ) met the inclusion criteria of the present study. PROMs such as the oral health impact profile 14 (OHIP-14), short-form health survey-36 (SF-36), World Health Organization QOL-BREF (WHOQOL-BREF), sence of coherence questionnaire-29, VAS, and patient atisfaction questionnaire have been used in single or multiple studies investigating the impact of orthognathic surgery on QOL (Zamboni et al, 2019). These PROMs have not been validated for measuring orthognathic QOL in patients with a cleft.…”
Section: Results Compared To Previous Researchmentioning
confidence: 99%
“…14 y Zamboni y cols. 15 indicaron que la presencia de problemas de sensibilidad no generó problemas de satisfacción en los pacientes, manteniéndose alta como en nuestro estudio. Sin embargo, otros estudios 3,12,16 reportaron que pacientes con tendencia a experimentar insatisfacción con la cirugía, se relacionaba con pérdida de sensibilidad de alguna región anatómica, junto con dificultad para masticar e inflamación.…”
Section: Discussionunclassified